1999
DOI: 10.2165/00003495-199957050-00003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Risk Factors for Hypertension

Abstract: We review the present knowledge of risk factors for arterial hypertension. Both genetic and environmental factors as well as their interaction and biological plausibility are reviewed. Recent data confirm that the interaction of genetics with multiple environmental risk factors explains the high prevalence of hypertension in the industrialised countries. The most important modifiable environmental risk factors are high salt intake, alcohol intake, obesity and low physical activity. The role of stress in the ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 159 publications
1
20
0
Order By: Relevance
“…Even though there are well-known definitions of hypertension used in Sweden, one could expect that the actual diagnostic threshold varies between physicians and over time. A study from 2003 reported hypertension prevalence in Sweden being approximately twice as high as in our study[17] In a recent study from the Netherlands, somewhat lower effect estimates associated with road noise exposure were seen when self-reported antihypertensive treatment were used rather than actual blood pressure measurements and pharmacy reports[15]…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Even though there are well-known definitions of hypertension used in Sweden, one could expect that the actual diagnostic threshold varies between physicians and over time. A study from 2003 reported hypertension prevalence in Sweden being approximately twice as high as in our study[17] In a recent study from the Netherlands, somewhat lower effect estimates associated with road noise exposure were seen when self-reported antihypertensive treatment were used rather than actual blood pressure measurements and pharmacy reports[15]…”
Section: Discussionmentioning
confidence: 63%
“…The coherence was lower among younger respondents and among men. We investigated confounding from variables a priori considered to be possible risk factors for hypertension: [19] sex, age, BMI, exercise, education, alcohol consumption, smoking and socioeconomic status. Smoking was included even though there is some controversy whether it leads to hypertension or not.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension is a multifactorial disease caused by various environmental and genetic factors. Aging, obesity, drinking, and lack of exercise are regarded as risk factors for hypertension 5 . Identifying the potential risk factors and predicting hypertension can help us understand the physiological mechanisms associated with blood pressure, improve the treatment of hypertension, and prevent hypertension.…”
Section: Association Between Hemoglobin Variability and Incidence Of mentioning
confidence: 99%
“…Counseling is tailored to individuals who are diabetic, 5658 African American, 59, 60 recently diagnosed with hypertension, and/or have hypertensive relatives 61, 62 because these factors confer specific risks for worse health outcomes.…”
Section: Figurementioning
confidence: 99%